SISTEM INFORMASI PENANGGULANGAN BENCANA PADA BPBD KABUPATEN MUARO JAMBI BERBASIS WEBSITE - Sri Mulyati; M. Najmi (JURNAL AKADEMIKA)
Regional Disaster Management Agency (BPBD) is a non-departmental government institution responsible for the implementation of disaster management in the area of both provincial and district / city based on the policies defined by the National Coordinating Board for Disaster Management . BPBDs established by Presidential Decree No. 8 of 2008, replacing the Coordinating Unit for Disaster Management (Satkorlak) and Provincial Disaster Management Implementation Unit (Satlak PB) at district / city level, both of which are established pursuant to Presidential Decree No. 83 Year 2005. Regulation Law Number 24 Year 2007 on Disaster Management mandates in Article 35 and 36 so that each region in disaster management, disaster planning has. In more detail mentioned in the Government Regulation Number 21 of 2008 on the Implementation of Disaster Management.